Agro-socioeconomic profile of adopters and non-adopters of drainage technology in Dankuni basin of West Bengal - Patra, S K; Ray, R; Senapati, T K; Mukhopadhyay, A K (Journal of Agricultural Engineering, 2000)
A sample survey consisting of eight farm households each of adoption and nonadoption of drainage and alternative technology was conducted in the Serampore block of Dankuni basin in West Bengal during 1999 for a comparative economic evaluation. The results show that the adopting farm households have better place in terms of average size of family, education status and operational holdings as compared to the non-adopting counterparts. The value of total assets for agricultural operation is also higher for the adopting farms. The medium landowners by virtue of their forward looking attitude and willingness to adopt sub-surface drainage technology were able to extract potential benefits from crops. Unsuitability of most of the low land for cultivation due to acute drainage problem is observed in both categories of farms.